The Role of Altered CSF Dynamics in Remote Cerebellar Hemorrhage: A Case Series. (16th November 2020) - Wu, Esther; Anderson, Matthew; Thompson, Bradford; Klinge, Petra M
Abstract: INTRODUCTION: Remote cerebellar hemorrhage (RCH) is a rare phenomenon with only a few hundred cases reported in the literature. RCH is characterized by spontaneous bleeding in the posterior fossa following supratentorial craniotomy or spinal surgery. The cause of RCH is debatable, although a likely theory postulates that large CSF volume loss leads to "cerebellar sagging, " creating changes in infratentorial venous blood pressure resulting in RCH. METHODS: Seven cases of RCH following surgery were collected from the Rhode Island Hospital medical records from 2017–2019. Information on patient demographics, comorbidities, procedures, development of RCH, treatment, complications, and outcomes were collected. A literature review was completed on PubMed using the keywords "remote cerebellar hemorrhage" and "postoperative cerebellar hemorrhage." RESULTS: The cases in this study suggest that CSF loss plays a direct role in the pathophysiology of a subset of RCH. Three of seven patients had postoperative changes in CSF dynamics. Of these, two were presumed to have CNS hypotension resulting from CSF leak after spinal surgery (lumbar fusion and thoracic laminectomy). One case involved VP shunt overdrainage which lead to RCH and required suboccipital craniectomy and adjustment of shunt settings. The other four patients without postoperative changes in CSF dynamics included patients who developed RCH following subdural hematoma evacuation. Three of these patients were asymptomatic and pursued no further treatment. One was symptomatic but the patient's family did not pursue further treatment due to the patient's age and comorbidities. CONCLUSION: In summary, CSF dynamics seem to play a key role in the development of RCH. Our study provides further insight into this rare condition, and further studies are needed to better understand the underlying mechanisms of RCH and identify opportunities to prevent it.